Vitamin D and periodontitis: shedding the light. (2nd December 2021) - Rattu, Varkha; Parmar, Jay; Raindi, Devan
Abstract : Periodontitis results from dysbiotic periodontal microbiota eliciting an exaggerated host immune-inflammatory response within susceptible individuals. With traditional biofilm management only partially effective, it became apparent that the individual's host response played a pivotal role in the pathogenesis of periodontitis. Specific nutritional factors have been found to impact the host response. Understandably, this has contributed to the emerging shift in contemporary research towards biological approaches to novel periodontal therapies. Vitamin D deficiency, a global public health problem, has been linked to numerous inflammatory conditions including periodontitis. The effects of vitamin D are multifaceted, favouring periodontal health and consideration should be given to its application in clinical practice. CPD/Clinical Relevance: The mechanisms and evidence implicating vitamin D as a host modulator of periodontitis are of relevance in periodontal therapy.